Ultrahigh plateau-capacity sodium storage by plugging open pores - Peng, Jiao (2025)
Hard carbon (HC) stands out as the most promising anode material for sodium-ion batteries (SIBs), and a precise adjustment of the pore structure is the key to achieving high plateau-capacity. In this work, composite hard carbon is developed by integrating graphitic carbon with biomass waste (banana peel)-derived activated carbon (AC). In this design, N-doped pseudographite layer is stacked at the entrance of open pores, forming a long-range graphitic layer without excessive graphitization. As a result, the surface area of AC is decreased by 170 times down to less than 10 m3 g-1, and the corresponding open pores are in situ converted into closed pores. In an optimized electrolyte solvation structure, the obtained HC anode achieves the reversible sodium-storage capacity up to 524 mAh g-1. In particular, a large portion of the capacity (490 mAh g-1) lies below the plateau of 0.25 V, which originates from the pore-filling mechanism as revealed by in situ Raman. This study provides a straightforward method to modulate the pore structure of carbon materials, and an energy-efficient (900 °C) synthesis for HC compared to traditional high-temperature routes (e.g., ≈1300-2000 °C).